Bemessung von Erzeugnissen aus Stahlguss unter vorwiegend ruhender Beanspruchung - Spannaus, Max Jonas (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2016)
Since the internal condition directly influences the calculated component resistance by using cast steel, the requirement of a quality grade already has to be determined during the design and planning phase. However, there is currently no decision-making on the selection of a quality level depending on the load. Therefore, two design concepts are developed for the load-bearing capacity of steel castings depending on the grades.